2005
DOI: 10.1002/art.21543
|View full text |Cite
|
Sign up to set email alerts
|

Variations of neuronal nitric oxide synthase in systemic sclerosis skin

Abstract: Objective. In systemic sclerosis (SSc), derangement of the peripheral nervous system is linked to vascular tone dysfunction. Nitric oxide (NO) produced by neuronal nitric oxide synthase (nNOS, NOS-I) might play a dynamic role in the control of vascular tone. This study was performed to verify, by immunohistochemical and biochemical analyses, the presence and expression of nNOS and protein gene product 9.5 (PGP 9.5) in SSc skin, in different subsets and various phases of the disease.Methods. Biopsy samples of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 30 publications
2
15
0
Order By: Relevance
“…The glands and the other skin appendages have been shown to be preserved, although reduced in number, even in the advanced skin pattern of the disease [29]. VEGF-C is expressed in the immature cells of sebaceous glands in an animal model of cutaneous wound healing [19].…”
Section: Discussionmentioning
confidence: 99%
“…The glands and the other skin appendages have been shown to be preserved, although reduced in number, even in the advanced skin pattern of the disease [29]. VEGF-C is expressed in the immature cells of sebaceous glands in an animal model of cutaneous wound healing [19].…”
Section: Discussionmentioning
confidence: 99%
“…Total cutaneous innervation and nNOS innervation slowly disappear in the skin of SSc patients [36]. Expression of nNOS depends on the severity of tissue damage in SSc, and increased synthesis of NO also contributes to this process [36]. Although previous studies have reported that circulating concentrations of most angiogenic factors were significantly higher in patients with SSc, there are no clear explanation for these elevation.…”
Section: Vascular Abnormalitymentioning
confidence: 97%
“…NO produced by neuronal nitric oxide synthase (nNOS, NOS-I) might play a dynamic role in the control of vascular tone. Total cutaneous innervation and nNOS innervation slowly disappear in the skin of SSc patients [36]. Expression of nNOS depends on the severity of tissue damage in SSc, and increased synthesis of NO also contributes to this process [36].…”
Section: Vascular Abnormalitymentioning
confidence: 99%
“…A large body of evidence has demonstrated that NO plays a key role in SSc physiologic and pathologic events, yet still controversial: either positive or negative effects at the microvascular level have been found in SSc skin [66]. Interestingly, besides the impairment of endothelial and inducible NO synthase activity in SSc [67,68], skin neuronal NO synthase was found to be down-regulated [69], and sympathetic skin impairment might have a role. In a recent study on a mouse model for hemiplegia-induced protection from RA, an impact on microvasculature was hypothesized [70].…”
Section: Discussion and Literature Reviewmentioning
confidence: 98%